Performance assessment of a novel solar distiller with a double slope basin covered by coated wick with lanthanum cobalt oxide nanoparticles. (April 2022) - Ghandourah, Emad Ismat; Sangeetha, A.; Shanmugan, S.; Zayed, Mohamed E.; Moustafa, Essam B.; Tounsi, Abdelouahed; Elsheikh, Ammar H.
Abstract: Solar distillers are simple desalination systems used to produce freshwater from saline water by utilizing solar energy. The low water yield is the key drawback of solar distillers. In this work, a novel double slope wick type solar distiller (DSWSD) coated with lanthanum cobalt oxide (LaCoO3 ) nanoparticles doped in black paint is experimentally investigated. The nano LaCoO3 /black paint is uniformly speared on the jute wick surface to boost the absorption improvement of solar irradiance for effective desalination. The influence of water flow rate (namely; 0.050, 0.10, and 0.20 kg/min) on the internal mass and heat transfer of the proposed DSWSD is analyzed. The mass and heat transfer coefficients (HTCs) are computed using the experimental results and compared with those computed according to Dunkle's correlations. Experiments have been conducted on the established DSWSD under climatic conditions of Vijayawada, Andhra Pradesh (16.4419° N, 80.6226° E), India. It is observed that there is an increase in the internal HTCs as well as distilled yield at low flow rates of saline water for the DSWSD. The daily productivity of the proposed DSWSD coated with and without 20 wt % LaCoO3 /black paint is 5.40 and 3.85 kg/m 2 . day, respectively, at saline water flow rate of 0.05 kg/min. Moreover, the average values of evaporative and convective HTCs as well as energy efficiency are found higher by 11.20%, 17.54%, and 24.86%, respectively, than that of the solar distiller without LaCoO3 /black paint.